Environmental claims in Indian print advertising: an empirical study and policy recommendation. Issue 3 (7th August 2017) - Prasad, Mousami; Mishra, Trupti; Kalro, Arti D.; Bapat, Varadraj
Abstract : Purpose: Environmental claims in advertising (green ads) provide competitive advantage to firms. This study aims to understand what kinds of environmental claims advertisers make in a developing nation like India. Further, implications for policymakers and advertisers are discussed. Design/methodology/approach: A content analysis of 279 green print advertisements was conducted using a comprehensive list of claim categories identified from the advertising literature. These categories included advertiser profile; ad promotions – type, sector, appeal; claim – nature, type, focus, validity, emphasis; executional elements – illustration setting, presenter, format/structure and environmental issue, identified from past studies and practitioner interviews. Findings: The findings suggest that majority of the advertisers using green ads are manufacturers. Consumer durables, real estate and power sector together constitute one-third of the total green ads. Further, most of the green ads are aimed at influencing consumer behaviour. Though most of the ads contain strong emphasis on environmental attributes, they are ambiguous. A large proportion of claims are credence in nature and lack product identification through environmental certifications. This study also identifies areas of concern including interpretation of the term green, use of multiple certifications, greenwashing and advertisers showing environmental responsiveness through event-based green advertising. Policy recommendations are made based on green advertising regulations governing them across developed and other developing countries. Research limitations/implications: The content analysis of the green advertisements in this study was limited to newspaper advertisements within the print media. Future studies may use advertisements from different media types, such as the internet ads and television commercials, to examine the effect of media type on the nature of green advertisements. It would also be interesting to examine the role of regulations as a moderator, influencing the claims made in green advertisements. Practical implications: The findings of this study provide a comprehensive overview of the nature of green advertisements in India. Marketers may use these insights to design effective green advertising strategies. Originality/value: Most of the extant literature has examined environmental claims in the context of developed nations, where regulations are well established. Very few studies have examined this issue in the context of developing countries. In addition, most of the previous studies have focused on specific issues like greenwashing, appeals and execution elements. The present study contributes to green advertising by examining environmental claims in case of a developing nation like India using a comprehensive list of claim categories. This study also identifies areas of concern and suggests recommendations for policymakers and advertisers.